Answer:
x = -6
Explanation:
∵
![(x)/(3)=(x+2)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/23uiej1uurg07837wd4un9fwdqa0yabw7w.png)
* These are two equivalent fractions
we can solve by using cross-multiplication way
that means we multiply x by 2 and multiply (x + 2) by 3
∴ 2(x) = 3(x + 2)
* Take care about the multiplication of 3(x + 2) you must
multiply 3 by x and also multiply 3 by 2
∴ 2x = 3x + 6
* Now lets start to collect the like terms
∴ 2x - 3x = 6
∴ -x = 6
* Divide the both sides by -1
∴ x = -6